Pengaruh Penggunaan Buku Saku oleh Motivator Terhadap Pengetahuan dan Ketrampilan Motivator dalam Mengatasi Permasalahan Pemberian ASI (di Kecamatan Sewon Kabupaten Bantul) - Nur Indah Rahmawati; Sri Achadi Nugraheni; Atik Mawarni (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2015)
Coverage of exclusive breastfeeding in the District of Sewon still low, either because they are less optimal role of KP motivator. They lack of conﬁ dence in dealing with problems in breastfeeding. The research objective was to analyze the effect of the use of a handbook by the motivator of the knowledge and skills motivator in dealing with problems in exclusive breastfeeding in the District of Sewon Bantul. This research is pre experiment with the design of nonequivalent one group pre test and post test design. The population was Motivator KP Capital in District Sewon many as 50 people. Collecting data through questionnaires and observations then performed univariate analysis (descriptive), bivariate (Paired T test). The results of research showed that the respondent’s average age was 46.74. Education respondents mostly high school was 25 people, most of the respondents did not work that 31 people (62%). Motivator knowledge prior to intervention use a pocket book value of the average was 64,5 while the value after the intervention mean value is 72.1. Motivator skills during pretest score was 57.6 at, while the second posttest mean value is 64.65. There was the effect of using a pocket book support group of mothers about breastfeeding, the problem of skills variable (p-value=0.0001) means the use of a paperback book motivators inﬂuencing skills in breastfeeding issues. Suggested for Health Department and Community Health Center in order to develop a motivator as refresher training for, to improve the knowledge and skills motivator in breastfeeding issues so as to increase the coverage of exclusive breastfeeding.